Dispute Settlement Reports 1997. World Trade Organization. (Cambridge University Press, 2000)
The Dispute Settlement Reports of the World Trade Organization (WTO) include Panel and Appellate Body reports, as well as arbitration awards, in disputes concerning the rights and obligations of WTO members under the provisions of the Marrakesh Agreement. These are the WTO authorized and paginated reports in English: as such, they are an essential addition to the library of all practising and academic trade lawyers, and will be widely consulted by students taking courses in international economic or trade law. DSR 1997: II contains Appellate Body and Panel reports on the 'bananas case' concerning the European Communities' regime for their importation, sale, and distribution. The form of citation recommended by the WTO for this volume is DSR 1997: II.